'The Gilded Age of Fraternalism': Brotherhood and Modernism in 1920s America. (12th July 2016) - Hernandez, Miguel
Abstract : The growth of the American obsession with fraternalism has been the subject of several historical treatises all seeking to understand what drew men and women into the lodge. The 1920s however, are a period that is often overlooked and neglected. Fraternalism continued to be a powerful national influence during this decade, and across the country orders received a surge of new recruits in the years following the First World War. Although their lodges had plenty of applicants, many fraternal leaders were concerned about the state of their institution in this post-war era. This article aims to analyse the evolution in the fraternal market that took place in the 1920s by examining the rapidly modernizing society of the Jazz Age and discussing the changing priorities of America's men and women.